Laboratory manual of microbiology, biochemistry and molecular biology - Saxena, Jyoti; Baunthiyal, Mamta; Ravi, Indu (Jodhpur : Scientific Publisher, 2012)
Though many practical books are available in the market but this Laboratory Manual of Microbiology, Biochemistry and Molecular Biology is an unique combination of protocols that covers maximum (about 80%) of the practicals of various Indian universities for UG and PG courses in Bioscience, Biotechnology, Microbiology, Biochemistry and Biochemical Engineering.
Keywords: Microbiology; Molecular Biology